2021
DOI: 10.1007/s10683-021-09726-7
|View full text |Cite
|
Sign up to set email alerts
|

What is considered deception in experimental economics?

Abstract: In experimental economics there is a norm against using deception. But precisely what constitutes deception is unclear. While there is a consensus view that providing false information is not permitted, there are also “gray areas” with respect to practices that omit information or are misleading without an explicit lie being told. In this paper, we report the results of a large survey among experimental economists and students concerning various specific gray areas. We find that there is substantial heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…This approach looks like deception. There is a strong norm against the use of deception in experimental economics; however, according to Charness et al 50 , precisely what constitutes deception is unclear, and they argued against a blanket ban, calling for a more nuanced view. Specifically, they mentioned that there is support for deception when the data are important, especially if this will not greatly impact any subject pool in the future.…”
Section: Methodsmentioning
confidence: 99%
“…This approach looks like deception. There is a strong norm against the use of deception in experimental economics; however, according to Charness et al 50 , precisely what constitutes deception is unclear, and they argued against a blanket ban, calling for a more nuanced view. Specifically, they mentioned that there is support for deception when the data are important, especially if this will not greatly impact any subject pool in the future.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, lying and deception are often considered synonymous and used interchangeably (e.g., Childs, 2012Childs, , 2013Dreber & Johannesson, 2008;Dugar et al, 2019;Erat, 2013;Gneezy, 2005;Gylfason et al, 2013), with a slight predominance of the former term (e.g., in lab experiments; Gneezy et al, 2018;Ben-Ner & Hu, 2021). However, recent contributions have defined and proven a clean difference between the two terms (e.g., Charness et al, 2021;Sobel, 2020). Sobel (2020) defines a lie as a statement that the sender knows to be false, and no evaluation of the implications of the lie-the motivation of the sender, the consequences for the receiver-is considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jamison et al 14 found no differences between participants who had or had not been deceived, though they did find some weak evidence that deceived women were less likely to participate in future experiments than were undeceived women. Further, in a survey of predominantly American students, 25% reported that they would be less willing to participate in future experiments if they knew they had been deceived 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental deception comes in many forms and there is often disagreement as to what precisely can be identified as deception 16 , 24 . Sieber et al’s 25 taxonomy identifies eight types of deception, from stating a false purpose to not informing subjects that they are part of a study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation